Effect of slurry ice during storage on myofibrillar protein of Pseudosciaena crocea. Issue 7 (4th June 2021) - Guan, Feng; Chen, Yirui; Zhao, Simin; Chen, Zhuo; Yu, Chen; Yuan, Yongjun
Abstract: In order to explore the effect of slurry ice on myofibrillar protein of Pseudosciaena crocea, the changes in myofibrillar protein and muscle microstructure during storage were studied with crushed ice as a control. During the storage period, the rate of decrease in myofibrillar protein content, Ca 2+ ‐ATPase activity, and total sulfhydryl groups in the slurry ice group was lower than in the control group ( p < .05). There was a significant linear correlation between the hydrophobicity and the storage time ( R crushed ice (4℃) = 0.9881, R slurry ice (4℃) = 0.9878, R slurry ice (−1℃) = 0.9674), and trichloroacetic acid (TCA) soluble peptide content was lower than in the control group at the same time. Slurry ice (−1℃) was optimal in maintaining protein content in P. crocea ; the arrangement of myofibrils in P. crocea treated by slurry ice was compact and the gaps were small. Slurry ice can delay the denaturation and degradation of fish myofibrillar protein and maintain its quality. Abstract : Slurry ice can delay the denaturation and degradation of fish myofibrillar protein. Slurry ice (−1℃) is the best one to keep protein of Pseudosciaena crocea . There was a linear correlation between the hydrophobicity and the storage time.